Pengaruh strategi kanal digital terhadap kinerja UMKM e-commerce di Indonesia: Analisis regresi logistik - Gilang Aldi Satria; Nur Andriyani (Nur Science Institute, 2026)
This study aims to analyze the determinants of e-commerce MSME performance in Indonesia by emphasizing the role of digital channel strategy, internal business capacity, and geographical location factors. The study uses cross-sectional secondary data from the 2023 E-commerce Survey conducted by Statistics Indonesia, covering 35,543 e-commerce MSMEs. Binary logistic regression was employed to examine the effects of marketplace usage, digital capability, information technology training, education, Java location, and the interaction between marketplace usage and location on the probability of increased business income. The results show that marketplace usage has no significant effect on the probability of improved business performance. In contrast, digital capability, information technology training, and education have positive and significant effects on the probability of increased business income. Business location in Java negatively affects the probability of performance improvement. Furthermore, the interaction between marketplace usage and Java location has a significant negative effect, indicating that the benefits of marketplace utilization in Java are lower than outside Java due to higher digital market competition. These findings suggest that the performance improvement of digital MSMEs is determined more by the internal capacity of business actors than by the type of digital channel used.